Allele and Haplotype Frequencies of HLA-A, -B, -C, and -DRB1 Genes in 3,750 Cord Blood Units From a Kinh Vietnamese Population - Que, Tran Ngoc; Khanh, Nguyen Ba; Khanh, Bach Quoc; Van Son, Chu; Van Anh, Nguyen Thi; Anh, Tran Thi Thuy; Tung, Pham Dinh; Thang, Nguyen Dinh (Frontiers in Immunology, 2022)
The frequencies and diversities of human leukocyte antigen (HLA) alleles and haplotypes are representative of ethnicities. Matching HLA alleles is essential for many clinical applications, including blood transfusion, stem cell transplantation, and tissue/organ transplantation. To date, information about the frequencies and distributions of HLA alleles and haplotypes among the Kinh Vietnamese population is limited because of the small sample size. In this study, more than 3750 cord blood units from individuals belonging to the Kinh Vietnamese population were genotyped using PCR sequence-specific oligonucleotide (PCR-SSO) for HLA testing. The results of the study demonstrated that the most frequently occurring HLA-A, -B, -C and -DRB1 alleles were A*11:01 (25%), A*24:02 (12.3%), A*02:01 (11.2); A*03:03 (8.95%), A*02:03 (7.81%), A*29:01 (7.03%); B*15:02 (15.1%), B*46:01 (10.7%), B*58:01 (7.65%), B*38:02 (7.29%); C*08:01 (17.2), C*07:02 (16.2%), C*01:02 (15.2), C*03:02 (8.3%), C*15:05 (6.13); DRB1*12:02 (31.0%), DRB1*09:01 (10.47%), DRB1*15:02 (7.54%); DRB1*07:01 (6.68%), DRB1*10:01 (6.63%), respectively, with the highest allele diversity level observed in locus B (93 alleles). The most frequent haplotypes of two-locus combinations of HLA-A–B, HLA-A–C, HLA-A–DRB1, HLA-B–C, HLA-B–DRB1, HLA-C–DRB1 haplotypes were A*11:01–B*15:02 (7.63%), A*11:01–C*08:01 (7.98%), A*11:01–DRB1*12:02 (10.56%), B*15:02–C*08:01 (14.0%), B*15:02–DRB1*12:02 (10.47%), and C*08:01–DRB1*12:02 (11.38%), respectively. In addition, the most frequent haplotypes of three- and four-locus sets of HLA-A–B–C, HLA-A–B–DRB1, HLA-A–C–DRB1, HLA-B–C–DRB1 and HLA-A–B–C–DRB1 were A*11:01–B*15:02–C*08:01 (7.57%), A*11:01–B*15:02–DRB1*12:02 (5.39%), A*11:01–C*08:01–DRB1*12:02 (5.54%), B*15:02–C*08:01–DRB1*12:02 (10.21%), and A*11:01–B*15:02–C*08:01–DRB1*12:02 (5.45%), respectively. This study provides critical information on the frequencies and distributions of HLA alleles and haplotypes in the Kinh Vietnamese population, accounting for more than 85% of Vietnamese citizens. It paves the way to establish an umbilical cord blood bank for cord blood transplantation programs in Vietnam.